Recuperación territorial, weychafes y vigilancias: Reflexiones sobre una economía moral de resistencia mapuche - Leone, Miguel (2022)
This article reflects on the moral economy existing in Mapuche spaces in a situation of resistance to the advance of forestry companies and Chilean state repression. It is based on several ethnographic notes taken in a visit to a Mapuche community particularly active in territorial recovery processes. Three axes structure the analysis: the logic of sabotage, the ethics of the weychafe (warrior), and the rationality of care and control. The text proposes to understand the practice of sabotage as a collective strategy of territorial recovery; identifies some of the main characteristics that the figure of the weychafe acquires today; and suggests that the constant police surveillance to which Mapuche activists in the Ngulumapu are subjected generates a “state of alert” that crosses the social space under study.